Penerapan Nilai-Nilai Etika Kristen Dalam Berbisnis - Sin'ear Purba (Management And Business Progress, 2026)
The Christian ethical perspective in understanding the business world is not solely focused on profit. Rather, it views business as a manifestation of one's faith-based responsibility to God and others, and understands it as a form of service. Therefore, the application of Christian ethical values in business, which is to glorify God through all business practices, must be understood and implemented based on God's Word. Business is a vital part of human life, and therefore requires a proper understanding based on true values. Christian ethics in business can provide appropriate guidance for the lives of believers to prioritize God, love, honesty, justice, wisdom, and humility. This is especially true for Christian businesspeople or other related parties, who understand business as a tool to serve God and glorify God by conducting business as an act of worship. This is the basis of Christian business ethics as God's calling in the business world to better serve this world for God's glory.